Immunoprofiles of colorectal cancer from Lynch syndrome. (2nd January 2019) - Walkowska, Joanna; Kallemose, Thomas; Jönsson, Göran; Jönsson, Mats; Andersen, Ove; Andersen, Mads Hald; Svane, Inge Marie; Langkilde, Anne; Nilbert, Mef; Therkildsen, Christina
ABSTRACT: Colorectal cancers associated with Lynch syndrome are characterized by defective mismatch repair, microsatellite instability, high mutation rates, and a highly immunogenic environment. These features define a subset of cancer with a favorable prognosis and high likelihood to respond to treatment with anti-programmed death 1 (PD-1)/programmed death ligand 1 (PD-L1) drugs. With the aim to define immune-evasive mechanisms and a potential impact hereof in colorectal cancers from Lynch syndrome versus hereditary cases with retained mismatch repair function, we immunohistochemically and transcriptionally profiled 270 tumors. Lynch syndrome-associated tumors showed an overrepresentation of tumor-infiltrating CD3, CD8 and CD68 positive cells, loss of beta-2-microglobulin (B2M) and up-regulation of PD-L1 on tumor cells. The gene expression signature of Lynch syndrome tumors was characterized by upregulation of genes related to antigen processing and presentation, apoptosis, natural killer cell-mediated cytotoxicity, and T cell activation. Tumors with loss of B2M and up-regulation of PD-L1 showed distinctive immunogenic profiles. In summary, our data demonstrate a complex tumor-host interplay where B2M loss and PD-L1 up-regulation influence immunological pathways and clinical outcome in Lynch syndrome tumors. Immunological classification may thus aid in the preselection of colorectal cancers relevant for treatment with anti-PD-1/PD-L1 therapies.